2017
DOI: 10.1589/jpts.29.1960
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of rib cage joint mobilization and chest wall stretch on muscle tone and stiffness of respiratory muscles and chest expansion ability in patients with chronic stroke

Abstract: [Purpose] The main purpose of this study was to identify the impact of rib cage joint mobilization and chest wall stretch on respiratory muscle tone and stiffness and chest expansion in stroke patients and to compare the effects of both interventions. [Subjects and Methods] Subjects were randomly assigned to a rib cage joint mobilization group (n=15) or a chest wall stretch group (n=15). Respiratory muscle tone and stiffness were measured using a myotonometer, and the chest expansion was gauged using a measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…In this study, the specific extending and attaching of tape to this muscle may have increased inspiratory resistance, thereby inducing the involvement of more respiratory muscles during breathing exercis. A previous EMG study3 ) supports the results of the present study, which is that the muscle activity of the affected UT and EO muscles in stroke patients increased after breathing exercise. However, given the possibility that diaphragm taping could be ineffective in improving respiratory strength12 ) , it is necessary to confirm the correlation between the muscle tone and stiffness of respiratory muscles and increases in respiratory strength through continuous research.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the specific extending and attaching of tape to this muscle may have increased inspiratory resistance, thereby inducing the involvement of more respiratory muscles during breathing exercis. A previous EMG study3 ) supports the results of the present study, which is that the muscle activity of the affected UT and EO muscles in stroke patients increased after breathing exercise. However, given the possibility that diaphragm taping could be ineffective in improving respiratory strength12 ) , it is necessary to confirm the correlation between the muscle tone and stiffness of respiratory muscles and increases in respiratory strength through continuous research.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, the abnormal muscle tone and stiffness shown in the extremity muscles of stroke patients9, 11 ) were similar to the tone and stiffness of their respiratory muscles. An electromyogram (EMG) study of the respiratory muscles of strokes patients3 ) showed lower levels of respiratory muscle activity on the affected side, similar to the findings of the present study. The results of this study may be important basic data that quantitatively show decreased muscle tone and stiffness in the affected respiratory muscles of stroke patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations